2014
DOI: 10.1002/14651858.cd009910.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial thermoplasty for moderate or severe persistent asthma in adults

Abstract: Analysis 1.1. Comparison 1 Bronchial thermoplasty versus control, Outcome 1 AQLQ final scores at 12 months of follow-up....... Analysis 1.2. Comparison 1 Bronchial thermoplasty versus control, Outcome 2 ACQ final scores at 12 months of follow-up........ Analysis 1.3. Comparison 1 Bronchial thermoplasty versus control, Outcome 3 Participants admitted to hospital because of respiratory adverse events (treatment period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 29 publications
0
44
0
8
Order By: Relevance
“…Clinical trials of BT have shown benefits in the treatment of patients with moderate to severe asthma Pavord et al 2007Pavord et al , 2013Castro et al 2010;Torrego et al 2014;Thomson et al 2011;Wechsler et al 2013]. Little is known about the safety and efficacy of BT when performed in clinical practice [Doeing et al 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials of BT have shown benefits in the treatment of patients with moderate to severe asthma Pavord et al 2007Pavord et al , 2013Castro et al 2010;Torrego et al 2014;Thomson et al 2011;Wechsler et al 2013]. Little is known about the safety and efficacy of BT when performed in clinical practice [Doeing et al 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up observational studies to date support the long-term safety of the procedure, based on unchanged rates of respiratory adverse events, lung function, serial computed tomography scans and rates of hospital admissions or emergency department visits in years 2-5 following the AIR [6], RISA [7] and AIR2 trials [8]. A Cochrane systematic review of the trials concluded that there was a modest clinical benefit in asthma quality of life and a reduction in exacerbation rates 12 months after bronchial thermoplasty [9]. In 2010, the Food and Drug Administration (FDA) gave premarket approval for the Alair bronchial thermoplasty system (Boston Scientific, Marlborough, MA, USA) as a treatment for severe persistent asthma in patients 18 years and older whose asthma is not well controlled with inhaled corticosteroids and a long-acting β-agonist [10].…”
mentioning
confidence: 99%
“…[28][29][30][31][32] However, add-on therapies, such as macrolides, anti-immunoglobulin E, tumor necrosis factor alpha inhibitors, cytokine receptor antagonists, and bronchial thermoplasty, are developing as alternative options in refractory asthma care. 33,34 Inhaled Versus Systemic Route of Short-Acting ␤-Agonist Administration According to the latest global strategy for asthma management and prevention report of the Global Initiative for Asthma, asthma treatment for adults is divided into controller and reliever categories, each administered via inhalation, orally, or parenterally (subcutaneous, intramuscular, or intravenous injection). Because inhaled medication is delivered directly to the site of the desired effect, and systemic side effect risk is relatively low, [35][36][37] this route is preferred.…”
Section: Discussion Current Evidence-based Asthma Management and Carementioning
confidence: 99%